'A fanzine of record': Merseysound and mapping Liverpool's post-punk popular musicscapes. (8th September 2011) - LASHUA, BRETT; COHEN, SARA
This article focuses on one particular fanzine – Merseysound – and how it provides a grassroots account of Liverpool's post-punk scene over a three-year period (1979–1982). The fanzine draws attention to the material and historical context of the post-punk scene and provides a rich and detailed mapping of the performance venues connected to it. This article begins by introducing Merseysound and explaining how it was produced. It is then divided into three sections in order to consider how the fanzine: (1) chronicled the emergence and development of Liverpool's postpunk music scene and connected it to conventional narratives of urban decline and renewal; (2) promoted the idea that the scene had one core venue; and (3) mapped other venues connected to the scene and relations between those venues. The case of Merseysound shows that fanzines are a useful historical resource for research on punk and post-punk. They provide a record of local punk and post-punk scenes but they were also active agents within those scenes, helping to create the groups, identities and ideologies involved. In this way fanzines can highlight the complex and dynamic relationships between music and place.